Meningkatkan Kepercayaan Pelanggan dalam Mengembangkan Kepuasan Pelanggan Melalui Kualitas Rekomendasi dan Kualitas Website pada Aplikasi LinkAja - Udayana, Ida Bagus Nyoman; Ningrum, Nonik Kusuma; Perkasa, Duta (Universitas Batanghari Jambi, 2024)
This study aims to determine the effect of Recommendation Quality and Website Quality in order to increase Customer Trust in developing Customer Satisfaction in the LinkAja application. Many people use e-wallet applications in their daily activities. In Indonesia, there are many e-wallet applications, for example LinkAja. This research will discuss how satisfied customers are in using LinkAja. There are three variables that affect customer satisfaction in this study. The three variables are recommendation quality, website quality, and customer trust. The research results show that website quality and customer trust variables have an influence on customer satisfaction.